Factors contributing to China's rise to power: an application of the balance of power theory - Yoo, Jin Yi (Nanyang Technological University, 2023)
This project investigates the factors that have led to China’s rise since its independence using the Hans Morgenthau’s balance of power theory. I argue that China was able to improve its position in the international system through strengthening its economic and military power. The project investigates two main factors of international power according to balance of power theory: economic (natural resources, industrial capacity, population), and military (geo-political factors and military preparedness). I argue that the improvement in national power contributed to China’s rise in international power. Past studies have focused on the China’s economic achievements, but I will depart from these studies by addressing the link between material (economic) and non-material (military) factors in China’s rise to power. By examining these elements of national power (economic and military), the project concludes that China’s rise to power can be attributed to the improvement in its economic and military capacities.